Factors affecting online buying behavior of youngsters towards footwear industry of Bangladesh - Sayefuddin Rakib, Mustafa Hamid (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.